A magnetic study of the subglacial ridge formed in the 1996 Gjálp eruption - Tryggvi Unnsteinsson 1995- (2018)
During the 1996 Gjálp eruption an approximately 6 km long subglacial tindar (hyaloclastite ridge) formed in a mostly subglacial fissure eruption beneath the Vatnajökull ice cap. By definition, tindars are composed of hyaloclastite and pillow lava in variable ratios. Hands-on observations on the top of the edifice shortly after the eruption found only pyroclastic materials but further direct observations were not possible due to meltwater and the engulfing of the edifice by the ice. A combined radio-echo and gravimetric study was conducted by Gudmundsson et al. (2002) to determine the shape and size of the Gjálp edifice and estimate its density. A central question was the ratio of pillow lava versus hyaloclastite in the edifice. Results indicated that the southern and central part of the edifice had little or no pillow lava and that the northern part might be partly composed of pillow lava but results were not conclusive. To study this question further, a magnetic survey of the area was suggested and carried out in 2002. Processing of this data and analysis of the profiles surveyed is presented in this theses. The analysis shows that the southern and central parts of the edifice are mostly or fully nonmagnetic. For the northern part the magnetic profiles over the edifice are consistent with a significant part of it being magnetized. This indicates that there is some pillow lava in the northern part of the Gjálp edifice while the central and southern parts appear to be solely made of hyaloclastite. Í Gjálpargosinu 1996 hlóðst upp móbergshryggur á um 6 km langri gossprungu undir Vatnajökli. Samkvæmt skilgreiningu eru móbergshryggir gerðir úr hýalóklastít og bólstrabergi í breytilegum hlutföllum. Athuganir toppi hryggjarins stuttu eftir goslok fundu einungis laus gosefni en fleiri beinar athuganir voru ekki mögulegar vegna bræðsluvatns og sökum þess hve fljótt jökullinn huldi hrygginn. Samhliða því að lögun hryggjarins var ákvörðuð með íssjármælingum voru þyngdarmælingar voru framkvæmdar af jarðvísindamönnum ...